Empirical Research on Bond Pricing: Discussion - Gibbons, Michael R. (Journal of Finance, 1983)
Michael R. Gibbons, Empirical Research on Bond Pricing: Discussion, The Journal of Finance, Vol. 38, No. 2, Papers and Proceedings Forty-First Annual Meeting American Finance Association New York, N.Y. December 28-30, 1982 (May, 1983), pp. 648-650